Photocatalytic Degradation of Chlorobenzene by TiO2 in High-Temperature and High-Pressure Water - N. Kometani; S. Inata; A. Shimokawa; Y. Yonezawa (International Journal of Photoenergy)
A fluidized-bed-type flow reactor available for the photocatalytic treatment of the suspension of model soil under high-temperature, high-pressure conditions was designed. An aqueous suspension containing hydrogen peroxide (H2O2) as an oxidizer and inorganic oxides as a model soil, titania (TiO2), silica (SiO2), or kaoline (Al2Si2O5(OH)4) was continuously fed into the reactor with the temperature and the pressure controlled to be T=20–400∘C and P = 30 MPa, respectively. The degradation of chlorobenzene (CB) in water was chosen as a model oxidation reaction. It appeared that most of the model soils are not so harmful to the SCWO treatment of CB in solutions. When the TiO2 suspension containing H2O2 was irradiated with near-UV light, the promotion of the degradation caused by photocatalytic actions of TiO2 was observed at all temperatures. Persistence of the photocatalytic activity in the oxidation reaction in high-temperature, high-pressure water would open up a possibility of the development of the hybrid process based on the combination of SCWO process and TiO2 photocatalysis for the treatment of environmental pollutants in soil and water, which are difficult to handle by conventional SCWO process or catalytic SCWO process alone.